RCBus: Row-Column Bus Topology for Optical Network-on-Chip - Fu, Weiwei; Chen, Tianzhou (Elektronika ir Elektrotechnika, 2012)
Future chip multi-processors (CMPs) will require high-performance yet low-energy networks-on-chip to provide scalable communication for the increasing number of cores. CMOS-compatible nanophotonic interconnects have recently emerged as a promising candidate for replacing traditional electrical network-on-chip, by providing high bandwidth chip-wide communication at low latency and power. In this paper, we utilize the emerging nanophotonic technology and propose RCBus, an optical network-on-chip topology in which multiple nanophotonic buses are uniformly distributed in each row and column of a two-dimensional torus network. Each bus employs a dense-wavelength-division-multiplexing optical waveguide to enable high-bandwidth express traversal along each dimension. We use multiple write single-read schemes and virtual channel based token protocol to implement light-speed arbitration and flow control. The optical-electrical interface is also studied in the paper. The proposed optical network-on-chip can exploit the advantages of both photonic bus and direct torus topology. Simulation results under synthetic and real-world application traffic show that RCBus is 2X better in terms of performance than the electrical mesh network-on-chip while saving nearly 30% power, and achieves on average 24 % throughput improvement at much lower cost compared to the state-of-the-art optical network. DOI: http://dx.doi.org/10.5755/j01.eee.18.8.2633